New Biotype of Vibrio cholerae O1 from Clinical Isolates in Surabaya - de Vries, Garry Cores; Sabdoningrum, Emy Koestanti; Rahardjo, Dadik (Institute of Topical Disease Universitas Airlangga, 2010)
A surveillance of new pathogenic variants of Vibrio cholerae O1 strains was initiated to identify the emerge and spread throughout Surabaya. Findings from seven years (1994–2000) and from years 2008 until now by using a two-fold surveillance strategy was pursued involving 1) hospital-based case recognition, and 2) environment samples. Rectal swabs and environment samples were transported to ITD-UNAIR, Surabaya for culture and isolates were characterized by serotypic identification and arbitrarily primed PCR fingerprints revealed a group of strains with similar fingerprint patterns that are distinct from those of the current El Tor epidemic strain. These strains have been analyzed by in vitro technique and the group has been denominated the Surabaya-Indonesian variant of V. cholerae O1.